Seismic forward modeling of a poly-metallic massive sulfide deposit at garpenberg, central Sweden - Ahmadi, O.; Juhlin, Christopher (European Association of Geoscientists and Engineers, EAGE, 2013)
The Garpenberg poly-metallic deposits are the largest massive sulfide of the base metals in Sweden. Since many shallow deposits will soon be mined out, there is a need to explore for deeper ore bodies. The seismic reflection method has been used in mineral exploration by many companies and researchers around the world. Based on these studies, it was decided to acquire a seismic reflection test profile in the Garpenberg area. After processing, some reflections were enhanced and interpreted to originate from horizons corresponding to the geology of the area. However, since one aim of the study was mapping and imaging of an ore body in the area, it was necessary to examine if the ore body had been imaged. Therefore, we decided to do forward modeling by a ray-tracing approach. The forward modeling can provide synthetic data that can then be processed the same as the real data. By comparison of the real and synthetic data, it was discovered that the imaging of the ore body was partly successful.